MEMBANGUN KEPUASAN UNTUK MENINGKATKAN LOYALITAS PADA FACEBOOK MARKETPLACE (Studi Kasus Konsumen Facebook Marketplace di Universitas Sarjanawiyata Tamansiswa Kampus 2 Jl.Kusumanegara 157 Yogyakarta ) - Eko Bagus Widakdhono; Ida Bagus Nyoman Udayana; Ambar Lukitaningsih (JURNAL EKOBIS DEWANTARA, 2021)
ABSTRAK This study aims to test the Hedonic Shopping Value and Ultitarian Shopping Value Against E-loyalty through E-satisfaction. This research was conducted on 80 respondents at Sarjanawiyata Tamansiwa Yogyakarta University Students with respondents using or buying Facebook Marketplace products. The results of this study indicate: 1) Hedonic Shoppping Value has a significant positive effect on E-satisfaction, 2) Ultitarian Shoppping Value has a significant positive effect on E-satisfaction, 3) E-satisfaction has a significant positive effect on E-loyalty, 4) Hedonic Shopping Value has no effect significant positive on E-loyaty, 5) Ultitarian Shopping Value has no significant positive effect on E-loyalty.